Developmental biology using purified genes : proceedings of the 1981 ICN-UCLA Symposia on Developmental Biology Using Purified Genes, held in Keystone, Colorado, on March 15-20, 1981 - Brown, Donald D., 1931- (ICN-UCLA symposia on molecular and cellular biology, 1981)
DEVELOPMNTL BIOL USING PURIFIED GENES Z.